STUDY OF MOTOR SKILL IN ELDERS FOR THE DEVELOPMENT OF A HIERARCHY OF REQUISITES TO THE DESIGN OF PRODUCTS - MELO, Ramon; REIS, Alexandre Amorim dos; BOSSE, Michaelle (Human Factors in Design, 2012)
<!-- /* Font Definitions */ @font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0;} @font-face {font-family:Cambria; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:auto; mso-font-pitch:variable; mso-font-signature:3 0 0 0 1 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Times New Roman"; mso-ascii-font-family:Cambria; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Cambria; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Cambria; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:PT-BR;} @page Section1 {size:612.0pt 792.0pt; margin:72.0pt 90.0pt 72.0pt 90.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0;} div.Section1 {page:Section1;} --> <p class="MsoNormal" style="margin-top: 0cm; margin-right: 19.85pt; margin-bottom: .0001pt; margin-left: 19.85pt; text-align: justify; text-justify: inter-ideograph; line-height: normal; mso-layout-grid-align: none; text-autospace: none;">This article gives examples on how to use knowledge related to human abilities on the development of a hierarchy of users’ request, helping and guiding an ergonomic project. The article presents different methods of classification of the human abilities and exemplifies with a tool that correlates aged users’ requests with the abilities needed to interact with automatic teller machines of banks.